SISTEM INFORMASI MONITORING DAN EVALUASI BELAJAR SISWA BERBASIS WEB DAN SMS GATEWAY DI SDIT NURUL ISTIQLAL KLATEN - Salisa Kurnia Sari, Dwi Remawati, Bebas Widada (STMIK Sinar Nusantara, 2017)
Nurul SDIT Istiqlal Klaten an Islamic-based elementary school that has a high awareness of the importance of the monitoring and evaluation of student learning in order to know the level of success of the learning process is running. In order to maximize the process it created an information system of monitoring and evaluation of student learning web-based and SMS-gateway. This information system can display a list of values of each student in each subject and grade of teaching a teacher with grouping based on the criteria of the KKM. Moreover, it can display a graph of the percentage of the value of grouping results. Values that have been added can be disseminated to parents / guardians of the students. This information system will display a graph the value of each student for all four test scores. System design using the Context Diagram, Hierarchy Process Input Output, Data Flow Diagrams, input design, output design, and database design. The result of this research is the information system of monitoring and evaluation of student learning which has an input in the form of student data, teacher data subject, the data homeroom, the data subject, class data, the data teacher, materials, values and information. While the results of the output of a graph of the results of grouping value, sms information listed value value with KKM and the average grade and disseminated the text contains some information. Based on the calculation of the questionnaire, obtained persentase 84,00% so that it can be concluded that the information system is feasible to implemention in SDIT Nurul Istiqlal Klaten. Keywords: Monitoring, PHP, SMS-Gateway